ANALYSIS OF DIGITAL CONTENT MARKETING TREND OF LOCAL START-UP BUSINESS IN NORTH SULAWESI - Rumbay, Wulandary E. T.; Mangantar, Maryam; Wangke, Shinta J. C. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Content marketing evolves to be a powerful marketing tactic in the digital, fast moving, information driven world. It is not a new strategy but more and more enterprises begin to engage in content marketing gradually. So what are the reasons of the rise of content marketing in todayâ€™s society? According to Rowley (2008) content marketing can be defined as a management process where a firm identify, analyze and satisfy customer demand to gain profit with the use of digital content distributed through electronic channels. There is a close relationship between marketing research and consumer behavior. They collect information about customers and potential customers in order to enhance the value of the market exchange for the customers. Customers today are smart and intelligent. They know they have the rights to choose what information to receive, in what kind of format that information is in and whether to believe the content (Hipwell & Reeves, 2013). This paper discusses about the use of content marketing in businesses and how it brings benefits to the companies. The conclusion summarizes six strategies companies use during the implementation of content marketing in their businesses.Â Keyword: content marketing, implementation, benefits, information